Food, economics, and health - Bhargava, Alok. (Oxford : Oxford University Press, 2008)
Drawing on the author's extensive and varied research, this text provides readers with a summary of concepts and issues in several disciplines including economics, nutrition, psychology and public health in the hope of improving the design of food policies in the developed and developing world.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Diet in disease; Food supply; Food -- Economic aspects; Food; Nutrition; Nutritionally induced diseases